1987
DOI: 10.1007/bf00021309
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of a plant promoter: S1 nuclease hypersensitive features of maize Adh1

Abstract: S1 nuclease was used to probe the architectural characteristics of the maize alcohol dehydrogenase-1 gene promoter. Three sites were identified as hypersensitive to S1 digestion in supercoiled, but not linear plasmids containing the Adh1 gene. The sites mapped to areas located 65, 330 and 800 base pairs 5' to the start of transcription. In each case, the strand specific nicking pattern was determined with nucleotide level precision. The -65 site was found to be a homopurine/homopyrimidine tract. The -330 site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…The 5'flanking sequence of the maize adhl gene contains severa1 near-and half-palindromic G-box elements, as shown in Figure 1 (Ferl and Nick, 1987;Ferl and Laughner, 1989), previously shown to have an in vivo footprint pattern similar to the Arabidopsis adh G-box (5'-CCACGTGG-3') (McKendree et al, 1990). These data suggest that GBF also interacts with the maize adhl promoter.…”
Section: G-box Binding Activity 1s Present In Maize Cell Suspension Ementioning
confidence: 56%
See 2 more Smart Citations
“…The 5'flanking sequence of the maize adhl gene contains severa1 near-and half-palindromic G-box elements, as shown in Figure 1 (Ferl and Nick, 1987;Ferl and Laughner, 1989), previously shown to have an in vivo footprint pattern similar to the Arabidopsis adh G-box (5'-CCACGTGG-3') (McKendree et al, 1990). These data suggest that GBF also interacts with the maize adhl promoter.…”
Section: G-box Binding Activity 1s Present In Maize Cell Suspension Ementioning
confidence: 56%
“…In both genes, transient expression studies have identified a complex array of positive regulatory elements in the upstream sequences, and, in maize adhl, enhancer-like elements able to confer anaerobic inducibility in either orientation have been found (Walker et al, 1987;Olive et al, 1990;McKendree and Ferl, 1992). In vivo detection of protein-DNA interactions by dimethyl sulfate footprinting revealed analogy among many of the binding sites of both the Arabidopsis adh and maize adhl5'flanking regions (Ferl and Nick, 1987;Ferl and Laughner, 1989). One such motif, 5'-GTGG-3', is present in three binding sites of the maize adhl promoter and in four sites of the Arabidopsis adh promoter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Putative recognition sequences for transcription factors are shown. Some of the motifs are repeated several times, including GC boxes (putative Sp1 binding sites), the CCACCA sequence, which has been described in the SV40 enhancer, though the identity of the putative binding factor(s) (HC3) is not known (28), and a motif, CCCGG, which is present in the maize Adh1 promoter (29). In addition, several binding sites that play a role in the induction of gene expression and in cell proliferation and differentiation were noted.…”
Section: ) or Hl60 Cells (Not Shown)mentioning
confidence: 99%
“…In plant systems, one example of this complexity is illustrated by the hexameric G-box (5'-CACGTG-3') and those DNA elements that contain small variations on this palindromic sequence, which we refer to collectively as G-box-like elements. In some cases these elements have been identified as targets for nuclear DNA-binding factors, examples of which include the light-regulated genes of ribulose-1,5-bisphosphate carboxylase/oxygenase (1), chlorophyll a/b binding proteins (2), and chalcone synthase (3), genes regulated by abscisic acid such as the Em gene of wheat (4) and the rabl6A gene of rice (5), as well as the stress-induced Adh gene of maize and Arabi-dopsis (6,7). The identification of these nuclear factors has prompted the isolation and characterization of 10 DNAbinding proteins specific for the G-box and G-box-like elements from four different plant species (4,(8)(9)(10)(11).…”
mentioning
confidence: 99%